احسان، مراقبہ، مشاہدہ اور کرامت کا مفہوم اور حقیقت لمعات التنقیح فی شرح مشکاۃ المصابیح کی روشنی میں تجزیاتی مطالعہ : An Analytical Study of Ihsaan, Murāqabah, Mushahada, And Karamah in The Light of Lamaʿāt Al-Tanqīh Fi Sharh Meškāt Al-Maṣābīḥ - Muhammad Yousuf; Dr. Hafiz Muhammad Sajjad (Al Manhal Research Journal, 2024)
This study investigates the concept of Ihsan (excellence or benevolence) within Islam, focusing on its two primary dimensions: self-care and kindness towards others. The research aims to understand how Ihsan influences individual behavior and contributes to community welfare. By analyzing the significance of Ihsan in both worship and daily interactions, the study emphasizes its crucial role in enhancing one's faith. Utilizing a qualitative methodology, the research incorporates textual analysis of Islamic teachings and scholarly interpretations. Key findings indicate that Ihsan consists of two main components: performing acts of kindness and executing good deeds with excellence, paralleling the notion of self-care. The study further identifies three levels of worship articulated by Sheikh Dehlawi: Obligatory Worship: Fulfilling mandatory religious duties. Worship with Intention: Engaging in worship that seeks Allah's pleasure and rewards. Divine Observation: Reaching a state of deep spiritual awareness where one feels immersed in the presence of Allah. Among these, prayer (Salah) is recognized as the highest form of worship, serving as a direct connection to Allah. The study also highlights the states of mushahada (witnessing) and murāqabah (observing) as essential experiences in the worship process. In conclusion, Ihsan is presented as a comprehensive framework that nurtures personal integrity and fosters community welfare. The findings assert that sincerity and humility in worship, along with a profound awareness of Allah's presence, are vital for achieving a complete and fulfilling faith. Overall, this research underscores the transformative potential of Ihsan in enhancing individual spirituality and promoting social harmony.